The internet usage among student in PTAR 1 to searching information / Nur Hartini Mohd Nawi - Mohd Nawi, Nur Hartini (2013)
This study identifies the pattern of Internet use among students at the Tun Abdul Razak Library (PTAR). It focuses on the frequency of students' use of the Internet for learning as well as the problems these students faced and also the satisfaction when they use the internet in that library. The population of this study comprises of 100 students from UiTM campus from semester 1 to semester 6. The qualitative methodology was used in the study and was done by distributing questionnaire. UiTM students are the main respondents. This study aims to determine Internet usage among students in searching their information in the library.